Genome-Wide Association Study Reveals the Genetic Basis of Five Quality Traits in Chinese Wheat - Hao, Shuiyuan; Lou, Hongyao; Wang, Haiwei; Shi, Jinghong; Liu, Dan; Baogerile,; Tao, Jianguang; Miao, Sanming; Pei, Qunce; Yu, Liangliang; Wu, Min; Gao, Ming; et al. (Frontiers in Plant Science, 2022)
Bread wheat is a highly adaptable food crop grown extensively around the world and its quality genetic improvement has received wide attention. In this study, the genetic loci associated with five quality traits including protein content (PC), gluten content (GC), baking value (BV), grain hardness (HA), and sedimentation value (SV) in a population of 253 Chinese wheat grown in Inner Mongolia were investigated through genome wide association mapping. A total of 103 QTL containing 556 SNPs were significantly related to the five quality traits based on the phenotypic data collected from three environments and BLUP data. Of these QTL, 32 QTL were continuously detected under at least two experiments. Some QTL such as qBV3D.2/qHA3D.2 on 3D, qPC5A.3/qGC5A on 5A, qBV5D/qHA5D on 5D, qBV6B.2/qHA6B.3 on 6B, and qBV6D/qHA6D.1 on 6D were associated with multiple traits. In addition, distribution of favorable alleles of the stable QTL in the association panel and their effects on five quality traits were validated. Analysis of existing transcriptome data revealed that 34 genes were specifically highly expressed in grains during reproductive growth stages. The functions of these genes will be characterized in future experiments. This study provides novel insights into the genetic basis of quality traits in wheat.